Diagnosis and Management of Left Atrium Appendage Thrombosis in Atrial Fibrillation Patients Undergoing Cardioversion - Melillo, Enrico (Medicina (Kaunas), 2019)
Atrial fibrillation is the most common cardiac arrhythmia and is associated with an increased risk of stroke and thromboembolic complications. A rhythm control strategy with both electrical and pharmacological cardioversion is recommended for patients with symptomatic atrial fibrillation. Anticoagulant therapy for 3–4 weeks prior to cardioversion is recommended in order to avoid thromboembolic events deriving from restoring sinus rhythm. Transesophageal echocardiography has a pivotal role in this setting, excluding the presence of left atrial appendage thrombus before cardioversion. The aim of this review is to discuss the epidemiology and risk factors for left atrial appendage thrombosis, the role of echocardiography in the decision making before cardioversion, and the efficacy of different anticoagulant regimens on the detection and treatment of left atrial appendage thrombosis.